Finance against poverty. - Hulme, David (Routledge, 1996)
This is the first of two volumes examining the theory that poverty in the world's poorest regions can be overcome through microeconomic policies. It provides a detailed analysis of this theory and offers policy recommendations for practitioners in this field.